Human error in medication administration process - Zyoud, Amr H.; Chew Abdullah, Nor Azimah (MCSER Publishing, Rome-Italy, 2016)
Context: Medication administration errors is continuous problem in hospitals and occur too frequently, error is unavoidable human action, since medication treatment is a risky procedure that deal with human live therefore error in this process can lead to dangerous consequences on patient well-being, traditionally nurses were blamed for those errors and considered as malpractice action since medication treatment is manly performed by nurses. Objectives: The current study examines the conditions that influence medication error in the perspective systemic approach.Methods: reviewing medication error contributing conditions topic is outlined, exploiting different perspective of how error occurs in medication process.Results and conclusion: the present study concluded that system approach permit a comprehensive set of contributing conditions underlying medication error to be recognize and addressed, rather than just adopt individual centered approach, Future studies should examine underlying conditions, in the perception of work practice environment conditions, team work conditions, task related conditions and individual conditions.